Immersive Platform for Neuroscience Experimental Studies - Rodríguez, Florencia (2017)
In this work, we present a computational toolkit to perform neuroscience experiments with people inside virtual immersive environment like a CAVE (Computer Assisted Virtual Environment). Several experiments can be designed, performed and measured for customized virtual scenes. Each participant is exposed to experiences in which they search and collect objects within a three-dimensional space, where they have to use spatial strategies to solve the task. The purpose is to study cognitive functions such as perception, attention, cognition and short term memory. These tools can reduce the time of experiments formulations and helps to discover mechanisms of attention and spatial and episodic memory. All information about each participant trajectory, the virtual scene configuration, the location of objects in these scenes, and answers to particular questions regarding the experience is collected and presented in.